If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 6(x + 3) = 48 Reorder the terms: 6x + 6(3 + x) = 48 6x + (3 * 6 + x * 6) = 48 6x + (18 + 6x) = 48 Reorder the terms: 18 + 6x + 6x = 48 Combine like terms: 6x + 6x = 12x 18 + 12x = 48 Solving 18 + 12x = 48 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + 12x = 48 + -18 Combine like terms: 18 + -18 = 0 0 + 12x = 48 + -18 12x = 48 + -18 Combine like terms: 48 + -18 = 30 12x = 30 Divide each side by '12'. x = 2.5 Simplifying x = 2.5
| 3g-4=12 | | 5x+8+7x-10+26-32-24x=46 | | 3f+6f=27 | | 27+1*4*16= | | 8e-3e=30 | | 14-3x=5-2x | | 9+1*6*216= | | 1+4-3*9= | | (x^2+2)+8x^2-6x(X^2+2)=0 | | 1-25*4*64= | | a=2(5a+a*9)+9 | | 42a^2-16=0 | | a=(5a+a*9)+9 | | X+0.25X=170 | | X+0.25X=180 | | X+25X=180 | | 135-3x=24x+21 | | 6+-3= | | 6(3-x)-5(2x-4)=4(3x)-14 | | 6(3-x)-5(2x-4)=4(-3x)+14 | | -2r+4r+2r=40 | | 10(x+4)-9(x-3)=8(x+13) | | 4k-1=3k+10 | | 7-4p=-3 | | 4k-5=8-2k | | 15-2t=3t | | -12=-28-4b | | 7x+5=6-8x | | 4x-15=x-8 | | 2x+1=5x-7 | | n+(n+20)+(3n-15)=180 | | 5-k=k+5 |